The influence of mining factors on seismic activity during longwall mining of a coal seam - Łukasz Wojtecki (International Journal of Mining Science and Technology, 2021)
In this article an attempt to determine the influence of mining factors on the seismic activity during the longwall mining of the upper layer of coal seam no. 405/2 in one of the Polish hard coal mines in the Upper Silesian Coal Basin was conducted. Two longwall panels were mined in analogous geological conditions and based on the same mining system and technology. However, there was significant difference with regards to the mining factors, which was reflected in the observed seismic activity. Some tools used in mining seismology were applied to illustrate the aforementioned influence of mining factors, e.g. the frequency-energy distribution, the frequency-magnitude distribution, the 2D distribution of released seismic energy, the relationship between released seismic energy and the volume of mined coal, the Benioff strain release, and the Gutenberg-Richter (GR) b coefficient distribution (b is the proportion between high and low energy tremors). Concerning the Benioff strain release, a new solution, based on the slope of a fitted line in a moving time window, is proposed.